2011
DOI: 10.1128/jb.01472-10
|View full text |Cite
|
Sign up to set email alerts
|

The sigE Gene Is Required for Normal Expression of Heterocyst-Specific Genes in Anabaena sp. Strain PCC 7120

Abstract: The filamentous cyanobacterium Anabaena (Nostoc) sp. strain PCC 7120 produces specialized cells for nitrogen fixation called heterocysts. Previous work showed that the group 2 sigma factor sigE (alr4249; previously called sigF) is upregulated in differentiating heterocysts 16 h after nitrogen step-down. We now show that the sigE gene is required for normal heterocyst development and normal expression levels of several heterocyst-specific genes. Mobility shift assays showed that the transcription factor NtcA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…5). Expression of sigE is shown to be up-regulated in differentiating cells at late stage of heterocyst differentiation using the sigE-gfp transcriptional reporter fusion (18), and SigE is involved in regulation of heterocyst-specific genes, such as nifH, fdxH, and hglE2 (19). In the present study, we showed that the transcription of sigE was up-regulated within 8 h after nitrogen deprivation, and NrrA regulated the sigE expression (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…5). Expression of sigE is shown to be up-regulated in differentiating cells at late stage of heterocyst differentiation using the sigE-gfp transcriptional reporter fusion (18), and SigE is involved in regulation of heterocyst-specific genes, such as nifH, fdxH, and hglE2 (19). In the present study, we showed that the transcription of sigE was up-regulated within 8 h after nitrogen deprivation, and NrrA regulated the sigE expression (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…NrrA Directly Regulates the sigE Expression-The sigE transcript is shown to increase 12 h after nitrogen deprivation in Anabaena PCC 7120 (19). Changes in the transcript level of sigE were examined at earlier stages of nitrogen deprivation.…”
Section: Nrra Positively Regulates Expression Of the Glgp1mentioning
confidence: 99%
See 3 more Smart Citations